2012
DOI: 10.1016/j.ejpb.2012.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of quality attributes of continuously produced granules using complementary pat tools

Abstract: Manufacturers of pharmaceutical solid dosage forms aim for a reduced production time and a shorter 'time-to-market'. Therefore continuous manufacturing gains increasing interest in the pharmaceutical industry. For continuous manufacturing, the quality of produced pharmaceuticals should be assessed in real-time (in-line, on-line and at-line) and not via the traditional off-line, often destructive and time-consuming analysis methods which supply the desired information only hours after sampling. This research pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 28 publications
(34 reference statements)
0
26
0
Order By: Relevance
“…Otsuka et al reported that various polymorphic forms of carbamazepine transformed into the dihydrate form during wet granulation and their dissolution of tablets obtained from their dried granules was delayed depending on the amount of hydrate during granulation. All of the previous studies reported that polymorphic transformation during granulation significantly affected the pharmaceutical properties of final tablet preparations, and induced variability of the products . Debnath and Suryanarayanan reported that THA transformed into THM during wet granulation and their THA tablets obtained from their dried granules were tested for their pharmaceutical properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otsuka et al reported that various polymorphic forms of carbamazepine transformed into the dihydrate form during wet granulation and their dissolution of tablets obtained from their dried granules was delayed depending on the amount of hydrate during granulation. All of the previous studies reported that polymorphic transformation during granulation significantly affected the pharmaceutical properties of final tablet preparations, and induced variability of the products . Debnath and Suryanarayanan reported that THA transformed into THM during wet granulation and their THA tablets obtained from their dried granules were tested for their pharmaceutical properties.…”
Section: Discussionmentioning
confidence: 99%
“…THA bulk powder in the pharmaceuticals was transformed into THM during storage and the wet granulation process, and the phase transformation of THA during processing affected the bioavailability of the products through their dissolution behaviors . To obtain high‐quality products, hydrate formation of THA during wet granulation with agitating and fluid bed granulators was studied quantitatively by in‐line NIR and Raman methods and multivariate analysis as real‐time analysis . Wikström et al reported in‐line monitoring of THA hydrate formation during high shear wet granulation using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…These examples demonstrate that Raman is an important on-line PAT in continuous synthesis. In secondary manufacturing, Fonteyne et al reported successful prediction of residual moisture content using on-line Raman and near-infrared and prediction of granule flowability using photometric imaging during a continuous granulation production [64]. …”
Section: Flow or Continuous Manufacturingmentioning
confidence: 99%
“…Single screw and twin-screw extruders for pharmaceutical granulation were introduced in the late 1980s and have been developed subsequently in recent years [16][17][18][19][20]. In one study, the semi-continuous extrusion wet granulation was compared with the high shear granulation using formulations containing varying lactose grades and an active pharmaceutical ingredient (paracetamol and cimetidine).…”
Section: Introductionmentioning
confidence: 99%